Combination of advanced oxidation processes and biological treatment for the removal of benzidine‐derived dyes. Issue 3 (3rd October 2013) - Castro, E.; Avellaneda, A.; Marco, P.
<x xml:space="preserve">Abstract</x> Dyes are widely used in the textiles industry in order to color their products. Textile industry consumes large volume of water and produce large amount of wastewater during all phases of textile production and finishing. The release of colored wastewater from these industries may present an ecotoxic hazard. Color removal and toxicity reduction, especially from textile effluents, have colossal challenge in recent decades, and up to now there is no single and cost‐effectively attractive treatment that can effectively decolorize and the dye effluent treatment. The objective of this review article is to propose a textile wastewater treatment technique from the environmental friendly. An attempt is made to define and evaluate the Advanced Oxidation Processes (AOPs) as efficient techniques for the treatment of industrial dyes and many other pollutants in textile industry wastewater. However, in general AOPs are not cheap techniques. By means of oxidation process, most pollutants will be converted into molecules, which, in general are better biodegradable. The feasibility of combining different AOPs and biotechnology techniques is considered and evaluated according to their decontamination efficiency of benzidine‐derived azo direct dyes used in the cotton textile industry. Ozonation in combination with aerobic biological treatment results as the more feasible system for color removal, total organic carbon, chemical oxygen demand, and toxicity reduction. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 873–885, 2014